Developing A Collaborative Governance Model for Stunting Reduction in Jeneponto Regency - Adi Hermawan; Rifdan; Nurussyariah; Muhammad Nur Yamin (Journal of Indonesian Scholars for Social Research, 2026)
Stunting represents a multidimensional human development challenge that requires cross-sectoral responses through sustained collaboration among diverse actors. Jeneponto Regency, as one of the regions with a relatively high prevalence of stunting, faces persistent difficulties in effectively integrating the roles of government institutions, communities, and non-governmental stakeholders. This study aims to develop a collaborative governance model for stunting reduction in Jeneponto Regency that strengthens coordination, policy integration, and program sustainability. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, field observations, and policy document analysis involving local government officials, relevant sectoral agencies, village administrations, health professionals, community representatives, and development partners. Data were thematically analyzed using a collaborative governance framework that emphasizes initial conditions, institutional design, collaborative processes, and collaborative outcomes. The findings reveal that collaborative efforts in stunting reduction remain constrained by fragmented authority, uneven actor capacity, and underdeveloped mechanisms of communication and inter-organizational trust. Nevertheless, significant opportunities for strengthening collaboration exist through the facilitative role of local government, enhanced village-level engagement, and the utilization of integrated data systems to support evidence-based decision-making. This study proposes a collaborative governance model that prioritizes cross-sectoral role integration, institutional strengthening, and sustained community participation. The model is expected to contribute theoretically to the advancement of public administration scholarship and provide practical policy recommendations for local governments seeking to accelerate stunting reduction in an effective and sustainable manner.